Pengaruh Profitabilitas, Likuiditas dan Ukuran Perusahaan Terhadap Struktur Modal - Ni Made Suryaningsih; Ida Ayu Surasmi; Cokorda Krisna Yudha (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2024)
Capital structure refers to the decision-making process regarding funding sources and the arrangement of funding options. In the mining sector, companies require substantial capital for resource exploration and corporate development. The study titled “The Impact of Profitability, Liquidity, and Company Size on Capital Structure” aims to investigate how profitability, liquidity, and company size influence the capital structure of mining firms listed on the Indonesia Stock Exchange. Utilizing a quantitative approach with secondary data, the research population comprises mining companies listed from 2020 to 2022. Through purposive sampling, 35 companies were selected for analysis. Multiple linear regression analysis was employed to analyze the data. Findings indicate that profitability negatively affects the capital structure of mining companies, as higher profits prompt firms to utilize retained earnings, thereby reducing the capital structure value. Liquidity also negatively impacts the capital structure, as companies with high liquidity levels tend to utilize assets to meet short- term obligations, consequently reducing the capital structure. Conversely, company size positively influences the capital structure, with larger companies exhibiting larger capital structures due to increased debt, while smaller companies have smaller capital structures.